2005
DOI: 10.1242/dev.01720
|View full text |Cite
|
Sign up to set email alerts
|

Direct association of Bazooka/PAR-3 with the lipid phosphatase PTEN reveals a link between the PAR/aPKC complex and phosphoinositide signaling

Abstract: Cell polarity in Drosophila epithelia, oocytes and neuroblasts is controlled by the evolutionarily conserved PAR/aPKC complex, which consists of the serine-threonine protein kinase aPKC and the PDZ-domain proteins Bazooka(Baz) and PAR-6. The PAR/aPKC complex is required for the separation of apical and basolateral plasma membrane domains, for the asymmetric localization of cell fate determinants and for the proper orientation of the mitotic spindle. How the complex exerts these different functions is not known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(172 citation statements)
references
References 81 publications
5
166
0
Order By: Relevance
“…Significantly, a double mutant, combining PTEN Y138L with an unphosphorylatable Thr366Ala mutation was able to support normal NMuMG cell lumen formation, unlike PTEN Y138L, removing the apparent requirement for protein phosphatase activity (Figure 6a, b). It has been proposed that PTEN's PtdInsP 3 phosphatase activity, targeted through interaction with PDZ-domain containing scaffolds, including Par3 is critical for its role in regulating epithelial morphogenesis [31,36,40]. Consistent with this proposal, a PTEN mutant unable to engage in PDZ-mediated protein protein interactions, PTEN Q399X, is also unable to rescue morphogenesis in PTEN knock down NMuMG cells (Figure 6a, b).…”
Section: Pten Regulation Of Epithelial Morphology Requires Both Lipidsupporting
confidence: 54%
“…Significantly, a double mutant, combining PTEN Y138L with an unphosphorylatable Thr366Ala mutation was able to support normal NMuMG cell lumen formation, unlike PTEN Y138L, removing the apparent requirement for protein phosphatase activity (Figure 6a, b). It has been proposed that PTEN's PtdInsP 3 phosphatase activity, targeted through interaction with PDZ-domain containing scaffolds, including Par3 is critical for its role in regulating epithelial morphogenesis [31,36,40]. Consistent with this proposal, a PTEN mutant unable to engage in PDZ-mediated protein protein interactions, PTEN Q399X, is also unable to rescue morphogenesis in PTEN knock down NMuMG cells (Figure 6a, b).…”
Section: Pten Regulation Of Epithelial Morphology Requires Both Lipidsupporting
confidence: 54%
“…Recent studies have revealed that PTEN not only regulates the P-AKT pathway, but also modulates the CDC42-Par signalling pathway, thus participating in the establishment of cell junctions and polarity 39 . Moreover, the PTEN protein itself can bind to the Par complex at tight junctions of epithelial cells [22][23][24] . Therefore, we examined whether loss of Pten affected cell polarity and spindle orientation of the two types of cells in the prostate tumours of Pten-mutant mice.…”
Section: Resultsmentioning
confidence: 99%
“…During asymmetrical cell divisions, cell polarity molecules such as Par complex (comprising of Par3, Par6 and aPKC) often function as a conserved polarity determinant to regulate spindle orientation and cell fate specification in both invertebrates and vertebrates [19][20][21] . In addition, accumulating evidence suggests that Par complex works together with PTEN to maintain epithelial polarity and to prevent epithelial tissue from tumorigenesis [22][23][24][25][26] . However, the expression patterns of these polarity molecules and the mechanisms by which they influence cell division modes of stem cells and tumorigenesis in the prostate are unknown.…”
mentioning
confidence: 99%
“…In support of this explanation, Prober and Edgar (2002) reported that Ras V12 activates the PIP 3 reporter only at the apical side of cells. Additionally, studies have shown that PTEN directly binds to the polarity gene Bazooka and that the activity of the PI3K pathway is polarized in Drosophila oocyte cells (von Stein et al, 2005). The activation of the PI3K pathway might, therefore, require the preservation of cell polarity, which could explain why Ras V12 does not induce the PI3K pathway if Dlg is lost.…”
Section: Discussionmentioning
confidence: 99%